2018
DOI: 10.1007/s10900-018-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Successful Implementation of a Shared Medical Appointment Model for Hepatitis C Treatment at a Community Health Center

Abstract: Highly efficacious direct acting antiviral (DAA) therapy for treatment of Hepatitis C Virus (HCV) infection is largely inaccessible to communities facing a shortage of available specialist providers. Though less demanding than previous interferon regimens, DAA therapy requires patients to adhere to 8-12 weeks of daily treatment, which can be challenging for some patient populations. Duffy Health Center, located on Cape Cod, Massachusetts, provides integrated medical, mental health and case management services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Previous studies have reported challenges in providing referrals, and this breakdown in collaboration and information sharing is a significant challenge to providing information, education, and access to HCV screening to individuals experiencing homelessness [ 13 ]. Because clients at both the social services organizations and their neighboring clinic partners overlap, a commitment to innovative, full integration can prove highly effective in increasing HCV screening and treatment, as researchers have shown in past studies [ 16 , 17 ]. Future studies should consider exploring the wide spectrum and variability of integration approaches within community-based organizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported challenges in providing referrals, and this breakdown in collaboration and information sharing is a significant challenge to providing information, education, and access to HCV screening to individuals experiencing homelessness [ 13 ]. Because clients at both the social services organizations and their neighboring clinic partners overlap, a commitment to innovative, full integration can prove highly effective in increasing HCV screening and treatment, as researchers have shown in past studies [ 16 , 17 ]. Future studies should consider exploring the wide spectrum and variability of integration approaches within community-based organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Ending the HCV epidemic requires expanding the type of providers who screen for, diagnose, and treat HCV to include those in non-traditional, community settings [ 16 , 17 ]. Community organizations can effectively screen, diagnose, navigate high-risk individuals into care, and retain them in HCV care [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2002, several primary care-based HCV programs have been described. 7,8,[17][18][19][20][21][22] Compared with these programs, the GLC is one of the oldest and single-site primary care-based HCV treatment programs in the United States. Several factors played a role in the longevity and growth of the GLC.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Several studies have described effective HCV management by primary care providers in various settings. [7][8][9][17][18][19][20][21][22] As such, in settings where there are leadership champions for elimination of HCV, various strategies can be used to identify, link, and navigate patients to cure of HCV infection.…”
Section: Lessons Learnedmentioning
confidence: 99%